MODERN ISSUES IN THE TREATMENT AND PREVENTION OF INFECTIOUS DISEASES - Durdona Otamuratova Umar qizi, (World Scientific Research Journal, 2025)
This article analyzes modern issues in the treatment and prevention of infectious diseases. The research examines the possibilities of reducing the spread of infectious diseases through early detection, effective treatment methods, and preventive strategies, as well as through the use of new technologies and innovative approaches. The article presents practical examples related to protecting public health, preventing epidemics, and improving the healthcare system.